Droplet charge estimates from charge and mass flux data - Pl. Yasslin Assin @ Salihin, Yassin. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The main objective of this project is to calculate the droplet's charge which radial trajectory paths is generally governed by its charge-to-mass ratio. The analysis of the droplet charge as a function of droplet diameter, spray current and atomizer boundary is necessary in order to model and predict the charged spray plume shape computationally. A commercially available software MATLAB, was used to calculate the droplet charge and Rayleigh limit ratio. The droplet charge increase with decreasing droplet diameter. The droplet velocity is reduced as droplet diameter reduced and well dispersed. These results show that the knowledge of droplet charge as a function of droplet diameter that can be utilized for optimum atomization process. The droplets charge was found to be less than the Rayleigh limit.